2019
DOI: 10.1109/tpwrd.2018.2843390
|View full text |Cite
|
Sign up to set email alerts
|

Thyristor/Diode-Bypassed Submodule Power Groups for Improved Efficiency in Modular Multilevel Converters

Abstract: The half-bridge Modular Multilevel Converter (MMC) is a Voltage Source Converter (VSC) with high efficiency, controllability and modularity. The topology is weak to DC side faults unless bipolar sub-modules are used, but this results in decreased efficiency. Power-Groups (PGs), a thyristor augmented multilevel structure, have been proposed as a way to reduce the power-loss increase arising from achieving DCfault-tolerance. This paper investigates whether the PG concept can also achieve significant efficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…6), while the amplitude of the MF component (83A) equals to the amplitude of icA. These all match with the arm current expression in (15). The voltage and current of the LF and MF ports are also demonstrated.…”
Section: ) Inner Current Loop Controlsupporting
confidence: 75%
See 2 more Smart Citations
“…6), while the amplitude of the MF component (83A) equals to the amplitude of icA. These all match with the arm current expression in (15). The voltage and current of the LF and MF ports are also demonstrated.…”
Section: ) Inner Current Loop Controlsupporting
confidence: 75%
“…10(c) shows the arm current iLA. It can be found that iLA contains the LF and MF components, matching with the expression in (15). Fig.…”
Section: B Experimentssupporting
confidence: 71%
See 1 more Smart Citation
“…where A pk is given by (17), while K um and K mo are the coefficients shown in (18) and (19), respectively. Finally, by combining the definition (20) with (22), the power ratio of the converter can be expressed as…”
Section: Power Capability and Selection Of Current-sharing Factormentioning
confidence: 99%
“…Both circuits reduce the total rating of the semiconductors and the energy storage elements compared to the MMC. The authors of [18], [20]- [22] propose variations of an FB-MMC where thyristor (or diode) switches are used for bypassing a converter arm or small groups of seriesconnected FB submodules (SMs), which leads to a significant loss reduction. Moreover, a thyristor-based half-bridge SM was proposed in [23], [24] for constructing a thyristor-based MMC with reduced conduction losses.…”
Section: Introductionmentioning
confidence: 99%